Study of Micro-discharges in Dielectric Barrier Discharge: Influence of Electrode Structure and Materials - Pandey, Manish; Khadka, Manoj; Thapa, Bhesh Bahadur; Tyata, Raju Bhai (Journal of Science and Engineering, 2025)
For the electrical characterization of Dielectric Barrier Discharge (DBD) at atmospheric pressure, various electrode systems were utilized. DBD was generated in air under atmospheric conditions and powered by a high AC voltage and high-frequency power supply. The current-voltage characteristics were analyzed for electrode gaps of 2 mm and 3 mm, varying the voltage from 0 to 12 kV while maintaining a frequency of 20 kHz for each electrode type (disk, cylindrical, and double cylindrical). In general, the number of micro-discharges (filaments) increased with rising voltage in each cycle. Notably, a stable glow discharge was observed in the double cylindrical electrode system at a 2 mm gap as the voltage varied. This configuration proved to be efficient, with the average power consumption being only one-third that of the single cylindrical electrode at the same gap. The energy dissipation for this system was calculated to be 18.25 μJ using power analysis and 16.74 μJ using the I-V characteristic curve.